Beware the villainess! 3 - Soda Ice; Berry, (Anime adapter) (Ize Press, 2025)
"Time to take out the trash. While staying at the Elizabeth manor, Melissa meets the last of the novel's male leads--the rich and fabulous Peacock Melody. And watching his attempts to buy the heroine's love, the last remnant faith she had in these men dies. Enough is enough. Melissa vows to keep these degenerates away from the sweet and innocent Yuri, the way only a villainess can!"--page [4] of cover.